»Tu smo – vaši smo« - prvi referendum o samoprispevku v Ljubljani - Vrečer, Nesa (Prispevki za novejšo zgodovino, 2023)
The present article examines the events leading to the first Ljubljana referendum on self-imposed contributions, representing the largest local self-imposed contributions in the Socialist Republic of Slovenia to that date. It analyses the influence of various factors that contributed to the decision to hold the referendum and the conditions in Ljubljana before 1971. In 1971, Ljubljana was facing a population increase, representing almost one-sixth of the population of the Socialist Republic of Slovenia. The shortage of educational and childcare institutions led to overcrowded conditions in existing schools. In 1967, a change in the law on education financing introduced the concept of communities of interest in education, enabling the financing of education through contributions from citizens, taxes, and other sources. Ljubljana encountered difficulties in financing education and childcare, sparking discussions about the introduction of self-imposed contributions. In 1971, a referendum was held, in which the majority of voters supported the introduction of self-imposed contributions to improve education and childcare. The referendum was accompanied by an intensive propaganda campaign that included a wide range of activities and ended with a convincing result, as nearly 58% of the voters expressed support for self-imposed contributions.
Keywords: izobraževanje; Ljubljana; referendum; samoprispevek; samoupravljanje